INTEGRATING CRITICAL THINKING SKILLS IN SECONDARY CHEMISTRY TEACHING: A SYSTEMATIC LITERATURE REVIEW - Doraisamy, D Sarasvati; Razak, Rafiza Abdul (LPPM Universitas Jambi, 2025)
Critical thinking (CT) is the core of the chemical education curriculum, yet it is generally in an inconsequential understanding and practice with second-level teachers. The research is a review of the previous studies of the integration of CT in teaching secondary chemistry. The research aims to find out how CT is conceptualised, taught and assessed by chemistry teachers and its consistency behind these practices. The systematic review was performed through the PRISMA 2020 guidelines. In total, 23 empirical studies of the period 2021-2025 were identified through using Scopus, Web of Science, ERIC and ScienceDirect. Important findings were extracted by thematic analysis. The Majority of teachers have an infusion style, which inserts CT into chemistry lessons based on inquiry, project-based learning, and socioscientific issues. The CT training and corresponding evaluation is scarce. Feedback and scaffolding are applied irregularly, though they are good. The beliefs of the teachers regarding the importance of CT, as well as its reality in the classroom, have a very distinct gap. Practices of assessment usually fail to respond to CT objectives. Future studies are required to come up with chemistry-specific models of CT and assessment instruments. Effective integration should be backed by professional development.